2018
DOI: 10.7759/cureus.2897
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Concomitant Emphysematous Cystitis and Clostridium difficile Colitis with Pneumoperitoneum

Abstract: Emphysematous cystitis (EC) is a rare condition described as air within the wall and lumen of the urinary bladder. It is a complicated form of urinary tract infection caused by gas-forming bacteria. Pneumoperitoneum described as gas in the peritoneum is usually seen with abdominal hollow organ perforation, and approximately 10% of cases have been reported that are not associated with abdominal hollow viscus perforation. To the best of our knowledge, no case of EC with pneumoperitoneum in the setting of concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…After a thorough literature review, we identified two reports of EC in the setting of infectious colitis [ 6 , 7 ]. Both of these patients had a history of type 2 diabetes mellitus, presented with C. difficile colitis, and had evidence of EC on CT scan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After a thorough literature review, we identified two reports of EC in the setting of infectious colitis [ 6 , 7 ]. Both of these patients had a history of type 2 diabetes mellitus, presented with C. difficile colitis, and had evidence of EC on CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these patients had a history of type 2 diabetes mellitus, presented with C. difficile colitis, and had evidence of EC on CT scan. However, only one of them had a concomitant UTI [ 6 ]. The presence of EC without any evidence of a UTI is not very common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gangrenous/emphysematous inflammation may occur in the stomach [33,66] (see Figures 16 and 17), esophagus [67], colorectum [68] (see Figures 15 and 18), urinary bladder [69,70], ureter [71], urethra [72], penis [73], epididymis/testis [74,75], endometrium [76], vagina [77], breast [78], bone [79], striated muscle [80], aorta [81], mediastinum [82], and endocardium [83]. Most cases are categorized in the nonclostridial etiology.…”
Section: Gangrenous/emphysematous Inflammation In Other Organsmentioning
confidence: 99%